Identification of Sexsual Behavior and HIV Insidence on Public Transportation Driver in Sidoarjo - Fufa Nandasari; Lucia Y Hendrati (Universitas Airlangga, 2015)
Human Immunodeficiency Virus (HIV) is a virus that can decrease the human immune system. The occurrence of disease is caused by interactions between agents, hosts, and the environment. in terms of the case of HIV-Acquired Immunodeficiency Syndrome (AIDS) from year to year in all parts of the world continues to increase, then this disease becomes a worrying health problem for the community, because in addition to not finding drugs and vaccines for prevention, this disease also does not cause symptoms during the course of the disease. This study aims to analyze sexual behavior that has a high risk of HIV incidence in public transportation drivers in Sidoarjo District, namely who is a sexual partner during the past month, the frequency of sexual relations other than his wife during the past month, and the use of condoms during intercourse other than his wife. A cross-sectional study with a population of all public transport drivers who came to take the Voluntary Counseling and Testing (VCT) examination. There were 62 respondents who came to participate in the examination and collected data through interviews by filling out the questionnaire and observation. The results showed that there were 5% of public transport drivers with HIV positive results, with risk behaviors of 22.8% having sexual relations with wives and sex workers, and 4.8% with sex workers alone, of these habits there were 62.9% when not using condoms. To reduce the risk of contracting HIV, efforts should be made to increase knowledge and motivate HIV risk behaviors.